Role of Nanotechnology in Electronics: A Review of Recent Developments and Patents - Payal; Pandey, Parijat (Recent Patents on Nanotechnology, 2022)
Background: Nanotechnology assures to be the base of the upcoming industrial revolution. The role that nanotechnology plays in electronic devices became a question of concern among the researchers when nanotechnology started to be the focal point of research programs in the developed and developing countries of the world. Nanoelectronics, formed by combining nanotechnology and electronics, deals with the handling, characterization, engineering, and manufacturing of electronic devices at the nanoscale. Method: By reducing the size of materials, their electronic properties alter, and inter-atomic interactions and quantum effects gain significant importance. The challenge lies in interpreting their electronic properties at nanoscale so that they can be exploited for use in new generation electronic devices. The need to trim downsize and have a higher component density have ushered us into an era of nanoelectronics. Results: This work presents a detailed review of nanotechnology, its approach towards nanoelectronics, classification and types of nanomaterials used in nanoelectronics, application areas of nanoelectronics and measuring instruments with characterization at nanoscale. Also, the work incorporates latest developments and patents in nanoelectronics. Conclusion: In this manuscript, the authors have reviewed different aspects of nanotechnology in the field of electronics, recent patents and related advancements.
Keywords: Nanotechnology